Wakaf Produktif dan Peranannya dalam Mengentaskan Kemiskinan di Indonesia - Yasniwati, Yasniwati (Nagari Law Review, 2023)
Waqf is one of the Islamic philanthropies that can help people get rid of poverty. Productive waqf is one of the economic media that we can use to help the government in terms of poverty alleviation. As one of the pillars of community welfare, waqf institutions have a significant role that can be felt by the community, especially in improving people's lives, especially when productive waqf is managed by professional nazhir such as schools established by waqf-based foundations where schools are free, then also the people who are around the school also feel the benefits such as they can trade around the school and the results of their efforts can help to fulfill their daily needs. The potential of productive waqf today if it is managed by a professional nazhir then productive waqf can realize people's welfare and help the government in eradicating poverty